Diagnosis of gastrointestinal parasites in reptiles: comparison of two coprological methods - Wolf, Denis; Globokar Vrhovec, Majda; Failing, Klaus; Rossier, Christophe; Hermosilla, Carlos; Pantchev, Nikola; Justus Liebig University Giessen (My University, 2014)
BACKGROUND: Exotic reptiles have become increasingly common domestic pets worldwide and are well known to be carriers of different parasites including some with zoonotic potential. The need of accurate diagnosis of gastrointestinal endoparasite infections in domestic reptiles is therefore essential, not only for the well-being of captive reptiles but also for the owners. Here, two different approaches for the detection of parasite stages in reptile faeces were compared: a combination of native and iodine stained direct smears together with a flotation technique (CNF) versus the standard SAF-method. RESULTS: A total of 59 different reptile faeces (20 lizards, 22 snakes, 17 tortoises) were coprologically analyzed by the two methods for the presence of endoparasites. Analyzed reptile faecal samples contained a broad spectrum of parasites (total occurence 93.2%, n=55) including different species of nematodes (55.9%, n=33), trematodes (15.3%, n=9), pentastomids (3.4%, n=2) and protozoans (47.5%, n=28). Associations between the performances of both methods to detect selected single parasite stages or groups of such were evaluated by Fishers exact test and marginal homogeneity was tested by the McNemar test. In 88.1% of all examined samples (n=52, 95% confidence interval [CI]=77.1 - 95.1%) the two diagnostic methods rendered differing results, and the McNemar test for paired observations showed highly significant differences of the detection frequency (P<0.0001). CONCLUSION: The combination of direct smears/flotation proved superior in the detection of flagellates trophozoites, coccidian oocysts and nematode eggs, especially those of oxyurids. SAF-technique was superior in detecting larval stages and trematode eggs, but this advantage failed to be statistically significant (P=0.13). Therefore, CNF is the recommended method for routine faecal examination of captive reptiles while the SAF-technique is advisable as additional measure particularly for wild caught animals and individuals which are to be introduced into captive collections.
Keywords: reptiles; parasites; coproscopic diagnostic; SAF-method; direct smear; ddc:630